2017
DOI: 10.1136/bjophthalmol-2017-310259
|View full text |Cite
|
Sign up to set email alerts
|

Trematodal granulomatous uveitis in paediatric Egyptian patients: a case series

Abstract: In Egypt, a unique pattern of granulomatous anterior uveitis in rural children attributable to a waterborne helminthic infection is reported. The River Nile and its fresh water fauna are implicated in our series, and the need for an environmental investigation to further outline best management options in the given endemic areas is highlighted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 21 publications
1
33
0
1
Order By: Relevance
“…Lesions were almost always recognized in young boys, as girls in these localities are not allowed to bathe or play in canal waters due to the conservative nature of the countryside. Similarly, other studies in both India and Egypt have reported that the majority of patients with anterior chamber granuloma were males and all were reporting bathing in local canal waters (Rathinam et al 2002;Arya et al 2016;Amin et al 2017;Amin et al 2019).…”
Section: Discussionmentioning
confidence: 56%
See 4 more Smart Citations
“…Lesions were almost always recognized in young boys, as girls in these localities are not allowed to bathe or play in canal waters due to the conservative nature of the countryside. Similarly, other studies in both India and Egypt have reported that the majority of patients with anterior chamber granuloma were males and all were reporting bathing in local canal waters (Rathinam et al 2002;Arya et al 2016;Amin et al 2017;Amin et al 2019).…”
Section: Discussionmentioning
confidence: 56%
“…Unlike other studies, we have not encountered patients with either lid or subconjunctival nodules. (Rathinam et al 2002;Arya et al 2016;Amin et al 2017) Amin and colleagues reported that complications at presentation, such as cataract, glaucoma, corectopia, phthisis or retrocorneal scarring, were present in 16% of their study eyes. (Amin et al 2017).…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations